ANNUAL TRAINING STRUCTURE FOR ATHLETES SPECIALIZED IN HURDLE RACING (Web of Teachers: Inderscience Research, 2025)
Hurdling is a complex and technically sophisticated discipline that requires careful and systematic preparation. Developing an optimal structure for year-round training will enhance the effectiveness of the training process and reduce the risk of injury. This work summarizes and analyzes the latest scientific research in the field of physical training for hurdlers, and proposes new methodological approaches based on modern understanding of running physiology and biomechanics. The results of this research can be used by coaches and athletes in developing individual training programs, improving athletic performance, and achieving high results in competitions.